PENGEMBANGAN ALAT PEMBERI MAKAN IKAN OTOMATIS MENGGUNAKAN ARDUINO - Mangaras Yanu Florestiyanto; Dessyanto Boedi Prasetyo; Moh. Hafidz Randy Handigar (Jurusan Teknik Informatika, 2019)
AbstractIn fish farming activities there are a number of important things that must be considered, namely feeding and controlling the quality of the water in the pond such as water temperature, pH level and water clarity, because these elements are important for fish growth and life. Adjusting the time to feed the fish is also very important so that the fish can stay alive, if it is too late to feed the fish the fish can be stressed and eventually starve to death. Fish owners who have a fairly busy level of activity, will feel a little difficulty when leaving the house in a long time, because meeting the needs of fish and continuous monitoring is very time consuming. Thus, an automatic fish feeding device was developed which can be adjusted when feeding and measuring the feeding. In this study, Arduino Uno and Arduino Mega 2560 are the